The Information Technology Effmts on Acoustic comfort in Exhibition Halls by Using ..Ecotect" program - al-Samurai, Safaa Uddin Husain; Mahmood, Rudhab Ahmed (Iraqi Journal of Architecture and Planning, 2018)